(untitled) (Journal of Parents and Teachers, 2016)
The Brave’s Club of School as Learning Community CPI Sansomendi IPI stems from the motivation to implement successful educational actions in the prevention of gender violence among peers. Such action has reduced conflicts comprehensively and now those students more valued among their peers are those to take a stand against violence. Students who break the silence are no longer considered coward, but brave.